Neoliberal Austerity: The Impact of Political Injustice on the Universal Right to Legal Aid Advocacy for Defendants Facing Indictment Within the Crown Court: A Precursor Towards a Miscarriage of Justice - Heslop, Jamie; Collie, Craig (The Wrongful Conviction Law Review, 2026)
Denying defendants access to legal aid places a detrimental infringement on the right to due process. Post-2010 in England and Wales it is evidenced that such rights are impacted by political fiscal policy. This contribution therefore considers how political interference through the implementation of neoliberal austerity may impact the due process of legal aid for defendants facing trial within the Crown Court. Concerning such a query, advocacy aspects of criminal legal aid will be considered and how funding of advocacy may impact the very foundations of due process. Furthermore, the research agenda narrows focus specifically on the Crown Court due to the potential severity indictable offences pose, especially if defendants face the possibility of being wrongfully convicted. Similarly, legal aid issues surrounding the causation of the barrister strikes are considered and how these may have helped or hindered the defendant’s access to due process. In the advent of the creation of neoliberal legislation, an investigation will be further carried out within the remit of the Legal Aid, Sentencing and Punishment of Offenders Act 2012 (LASPOA) which has possessed a detrimental grounding within the causation of creating a chain reaction towards a wrongful conviction within defendant’s facing an indictable based sentence.